2017
DOI: 10.1038/hdy.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of SSR and SNP markers for inferring the population genetic structure of the common fungus Armillaria cepistipes

Abstract: During the last years, simple sequence repeats (SSRs, also known as microsatellites) and single-nucleotide polymorphisms (SNPs) have become the most popular molecular markers for describing neutral genetic variation in populations of a wide range of organisms. However, only a limited number of studies has focused on comparing the performance of these two types of markers for describing the underlying genetic structure of wild populations. Moreover, none of these studies targeted fungi, the group of organisms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…As a result, it is fair to wonder how to conduct the tasks related to germplasm management, such as core collections construction, and the choice of the type of marker to be used is one of the first questions. Neutral SSR loci, due to slippage during replication, usually mutate much more frequently than SNP loci, leading to population-specific alleles that are useful for revealing population structure (Tsykun et al 2017). On the other hand, since they are usually developed in small numbers for one species, they therefore may not reflect genome-wide genetic diversity contrary to SNP loci that are much more frequent in the genome of most species (Ljungqvist et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is fair to wonder how to conduct the tasks related to germplasm management, such as core collections construction, and the choice of the type of marker to be used is one of the first questions. Neutral SSR loci, due to slippage during replication, usually mutate much more frequently than SNP loci, leading to population-specific alleles that are useful for revealing population structure (Tsykun et al 2017). On the other hand, since they are usually developed in small numbers for one species, they therefore may not reflect genome-wide genetic diversity contrary to SNP loci that are much more frequent in the genome of most species (Ljungqvist et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, microsatellite markers, once developed, can be used repeatedly in multiple studies, which may reduce their overall expense on a per-project basis [22]. Moreover, recent comparative studies in insects, fungi, and birds reported no major population genetic structural differences between these two approaches [23][24][25][26], or that more SNPs were required to produce the same information as a single microsatellite marker [27].…”
Section: Introductionmentioning
confidence: 99%
“…SSRs have been widely exploited as neutral markers in multitudes of studies such as ecology and evolutionary genetics, genome mapping, etc. irrespective of their hypermutablility [ 37 , 39 ]. SSRs are characterized by their inherent ability to cause frameshift mutations in genomic regions encoding phenotypic changes and therefore, confer an adaptive advantage in the course ofviral mutations [ 1 ]; Y.…”
Section: Introductionmentioning
confidence: 99%